2021
DOI: 10.1038/s41467-021-23988-y
|View full text |Cite
|
Sign up to set email alerts
|

Copper(I)-catalysed site-selective C(sp3)–H bond chlorination of ketones, (E)-enones and alkylbenzenes by dichloramine-T

Abstract: Strategies that enable intermolecular site-selective C–H bond functionalisation of organic molecules provide one of the cornerstones of modern chemical synthesis. In chloroalkane synthesis, such methods for intermolecular site-selective aliphatic C–H bond chlorination have, however, remained conspicuously rare. Here, we present a copper(I)-catalysed synthetic method for the efficient site-selective C(sp3)–H bond chlorination of ketones, (E)-enones and alkylbenzenes by dichloramine-T at room temperature. A key … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…However, radical-chain chlorination methods that involve chlorine radical (Cl · ) as the hydrogen-atom transfer (HAT) reagent, often exhibit poor C–H site selectivity. Consequently, benzylic chlorides are commonly prepared by the reaction of benzylic alcohols with SOCl 2 or via other functional-group interconversion methods. ,,,, C–H chlorination methods that employ species other than Cl · for the HAT step can show improved selectivity. In this context, Cu catalysts, in combination with N -fluorobenzenesulfonimide as the oxidant (Cu/NFSI), promote diverse C–H functionalization and oxidative cross-coupling reactions (e.g., Figure B) that exhibit high benzylic site selectivity. These methods involve a radical-relay mechanism, in which HAT generates a diffusible benzylic radical that undergoes subsequent functionalization by Cu II and a nucleophilic coupling partner.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, radical-chain chlorination methods that involve chlorine radical (Cl · ) as the hydrogen-atom transfer (HAT) reagent, often exhibit poor C–H site selectivity. Consequently, benzylic chlorides are commonly prepared by the reaction of benzylic alcohols with SOCl 2 or via other functional-group interconversion methods. ,,,, C–H chlorination methods that employ species other than Cl · for the HAT step can show improved selectivity. In this context, Cu catalysts, in combination with N -fluorobenzenesulfonimide as the oxidant (Cu/NFSI), promote diverse C–H functionalization and oxidative cross-coupling reactions (e.g., Figure B) that exhibit high benzylic site selectivity. These methods involve a radical-relay mechanism, in which HAT generates a diffusible benzylic radical that undergoes subsequent functionalization by Cu II and a nucleophilic coupling partner.…”
mentioning
confidence: 99%
“…The data in Chart 1 reflect isolated yields, with product volatility accounting for 1 H NMR yields in a few cases (1, 3−5). In addition, separation challenges resulted in several products being isolated as a mixture with unreacted C−H substrate (2,6,7,12,13,20,21). This issue is not considered problematic because the substrate will be inert in the subsequent reactions of the benzylic chloride and is readily separated at that stage (see below).…”
mentioning
confidence: 99%
“…With the reaction time set at 3 days, a continued survey of other solvents showed the azo coupling of the substrates with i-PrOH or t-BuOH instead of MeOH resulted in a further increase in product yield from 50 to 76% (entries 5 and 6). However, the analogous reactions performed with CF 3 CH 2 OH, DMSO-d 6 , EtOAc, THF or DMF as the solvent were found to lead to low product yields of 5-28% (entries [7][8][9][10][11]. Our studies subsequently showed that when the reaction was repeated in non-distilled t-BuOH at a slightly elevated temperature of 35 °C for 3 days, this gave the best result and provided the (E)-diazene product in 85% yield upon isolation (entry 12).…”
Section: Resultsmentioning
confidence: 99%
“…1e). 9 Under the appropriately developed reaction conditions, we envisaged a π-Lewis acidic gold(I) complex might favour C(sp 2 )-H bond insertion at the C3 position of the N-heterocycle over decomposition of the diazo motif of the α-diazocarbonyl compound. 10 As a consequence, this may allow the ensuing putative (1H-indol-3-yl) gold species that is directly formed in this manner to engage in azo coupling with the 1,2-and 1,4-diazoquinone to provide the corresponding (E)-3-arylazoindoles.…”
Section: Introductionmentioning
confidence: 99%
“…γ-Haloketones have also attracted considerable attention for their significant role as synthetic building blocks in the preparation of pharmaceutical products such as the antidopaminergic drug, droperidol, and the antidepressant drug, vilazodone . Hence, quite a few versatile synthetic protocols have been developed for γ-haloketones, such as ring opening halogenation of cyclobutanols, hydrogen halide mediated ring opening of cyclopropyl ketones, and CuOTf-catalyzed regioselective chlorination at secondary or tertiary γ-C–H bond of ketones …”
Section: Introductionmentioning
confidence: 99%